The Catholic Church in the modern age and the works of Marshall McLuhan an investigation into the dialogue between the church teachings on social communication and secular communication and media studies - Arriola, Joyce L. (Plaridel, 2024)
Access online through this link: https://www.plarideljournal.org/article/the-catholic-church-in-the-modern-age-and-the-works-of-marshall-mcluhan-an-investigation-into-the-dialogue-between-the-church-teachings-on-social-communication-and-secular-communication-and-media-stu